Head and neck infection, clinicopathological outline - Elmatri, Houssein H.; Gheryani, Nabeia A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Despite the antimicrobial drugs, a significant percentage of head and neck infection still can be recorded, this study try to identify the causes of recorded cases of head and neck infection in antibiotics era by focusing on the clinical presentation and the predisposing factors. Methods: A retrospective study was conducted in the department of otolaryngology in university of Benghazi including 84 patients who were diagnosed as head and neck infection. Clinical data, risk factors and managements were discussed in this study. Results: The 84 patients with deep cervical infection were studied. The mean age of our patients was 33 years, most of them were males. Some had other co-diseases. Their main complains was severe throat pain. The most common space involved was peritonsillar space and the most common source of infection was tonsillar infection. Only third of the cases showed positive culture results. The most common organism cultured was Staphylococci. The range of hospital stay was 4-11 days. There was no mortality in our series of patients. Conclusions: Cervical infection is associated with high rate of morbidity and mortality specially in immune-compromised patients, therefore early detection of the disease followed by quick and appropriate management are life-saving measurements. All patients need early broad-spectrum intravenous antibiotics, and most of them need different surgical intervention. As bad oral hygiene, smoking and low immunity are the major risk factors for neck infection, education of the community, especially in rural area, is required.